Health Sector Inflation Rate and its Determinants in Iran: A Longitudinal Study (1995–2008) - TEIMOURIZAD, Abedin (Iran J Public Health, 2014)
BACKGROUND: Health price inflation rate is different from increasing in health expenditures. Health expenditures contain both quantity and prices but inflation rate contains prices. This study aimed to determine the factors that affect the Inflation Rate for Health Care Services (IRCPIHC) in Iran. METHODS: We used Central Bank of Iran data. We estimated the relationship between the inflation rate and its determinants using dynamic factor variable approach. For this purpose, we used STATA software. RESULTS: The study results revealed a positive relationship between the overall inflation as well as the number of dentists and health inflation. However, number of beds and physicians per 1000 people had a negative relationship with health inflation. CONCLUSION: When the number of hospital beds and doctors increased, the competition between them increased, as well, thereby decreasing the inflation rate. Moreover, dentists and drug stores had the conditions of monopoly markets; therefore, they could change the prices easier compared to other health sectors. Health inflation is the subset of growth in health expenditures and the determinants of health expenditures are not similar to health inflation.